Analisis Risiko Keselamatan Dan Kesehatan Kerja (K3) Menggunakan Metode Hazard Identification Risk Assesment And Risk Control (HIRARC) Dan Job Safety Analysis (JSA) Di PT. Indo – Rama Synthtetics Tbk - Arlin, Shellfha Aprilia; Tarman, Tarman; Wibowo, Priyo Ari (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
This research was conducted at PT Indo-Rama Synthetics Tbk Purwakarta which is engaged in the Textile Industry. This research aims to analyze the risks of Occupational Safety and Health (K3) in the POY CP-3 Department at PT Indo-Rama Synthetics Tbk. The methods used are Hazard Identification, Risk Assessment, and Risk Control (HIRARC) and Job Safety Analysis (JSA). This department has a high level of risk because its production activities involve the use of high-speed machinery and chemicals, which have the potential to cause work accidents. Based on work accident data for the period September 2024 - March 2025, there were 7 accident incidents recorded, reflecting the lack of implementation of an OHS culture in the work area. Through the application of the HIRARC method, hazard identification, risk level assessment, and control recommendations were made for each work activity. The JSA method was used to analyze each stage of work to establish more specific control measures. The analysis results show that some activities have high to extreme risk levels, such as being squashed by trolleys and exposed to chemicals. Therefore, improvement proposals were made in the form of providing personal protective equipment (PPE), improving SOP , and regular work safety training. This research is expected to be a real contribution in increasing awareness and implementation of OHS, as well as a reference in efforts to prevent work accidents in the industrial environment.